Peripheral giant cell granuloma - Pushpendra Kumar Verma; Ruchi Srivastava; Akhilesh Chandra; Anju Gautam; Pramod Yadav (Wolters Kluwer Medknow Publications, 2013)
Gingival overgrowth is one of the most undesirable consequences that often lead to severe aesthetic changes and compromised oral hygiene maintenance. Giant cell granuloma is among the localized growths, considered to be reactive rather than neoplastic in nature. It is relatively a benign, nonodontogenic lesion of oral cavity. It is a reactive response to local irritations and trauma that may be of central or peripheral type. The purpose of this article is to report the clinical, histopathological features and treatment of a case of peripheral giant cell granuloma arising from maxillary anterior alveolus in a 37-year-old male. The lesion was completely excised to the periosteum level and there was no recurrence or bony defect apparent in the area of biopsy after a follow-up period of 8 months. Proper plaque control and effective oral hygiene can reduce its severity or prevent its occurrence.